Workshop: Pengenalan Grammarly sebagai Alat Bantu untuk Menulis Bahasa Inggris - Sibghatullah Mujadidi; Siti Suharsih; Amalia Nur Azizah; Putri Bahjah Salsabila; Tiara Fadia Savitri (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Writing is an essential communication skill that is needed in various aspects of life. Good writing skills play a crucial role in education and career. However, many people face challenges in writing, such as grammar errors, incorrect spelling, and inconsistency in writing style. The purpose of this workshop is to introduce and provide participants with an understanding of the effective use of Grammarly as a writing tool. The workshop discusses the benefits of Grammarly in improving grammar, spelling, and writing style, as well as providing instant feedback and suggestions in the writing process. The workshop speaker will clearly explain the use of Grammarly, describing its features, providing examples of its usage, and explaining how Grammarly offers suggestions and feedback in the writing process. The workshop has been successful and received positive responses from participants, who feel greatly helped in improving their writing skills and gaining a better understanding of Grammarly's usage.